The Hypothalamic-Pituitary-Adrenal Axis: Development, Programming Actions of Hormones, and Maternal-Fetal Interactions - Sheng, Julietta A.; Bales, Natalie J.; Myers, Sage A.; Bautista, Anna I.; Roueinfar, Mina; Hale, Taben M.; Handa, Robert J. (Frontiers in Behavioral Neuroscience, 2021)
The hypothalamic-pituitary-adrenal axis is a complex system of neuroendocrine pathways and feedback loops that function to maintain physiological homeostasis. Abnormal development of the hypothalamic-pituitary-adrenal (HPA) axis can further result in long-term alterations in neuropeptide and neurotransmitter synthesis in the central nervous system, as well as glucocorticoid hormone synthesis in the periphery. Together, these changes can potentially lead to a disruption in neuroendocrine, behavioral, autonomic, and metabolic functions in adulthood. In this review, we will discuss the regulation of the HPA axis and its development. We will also examine the maternal-fetal hypothalamic-pituitary-adrenal axis and disruption of the normal fetal environment which becomes a major risk factor for many neurodevelopmental pathologies in adulthood, such as major depressive disorder, anxiety, schizophrenia, and others.